Analisis Faktor Fundamental terhadap Harga Saham: Studi Empiris pada Saham IDX30 Periode 2024 - Rissa Aulia Safitri; Yusnizal Firdaus; Dwi Riana (Jurnal Manajemen Riset Inovasi, 2026)
The IDX30 Index consists of 30 companies with large market capitalization and high stock liquidity listed on the Indonesia Stock Exchange. However, throughout 2024, the index experienced relatively weak performance and frequently underperformed the Composite Stock Price Index (IHSG). This condition indicates that stock price movements are influenced not only by companies' fundamental performance but also by external factors affecting market sentiment. This study aims to examine the effect of Return on Assets (ROA), Return on Equity (ROE), and Debt-to-Equity Ratio (DER) on the stock prices of companies included in the IDX30 Index during 2024. A quantitative approach was employed using secondary data obtained from quarterly financial statements and closing stock prices of 23 companies that met the sampling criteria, resulting in 92 observations. Panel data regression was applied as the analytical method, with the Fixed Effect Model selected as the most appropriate estimation model. The findings reveal that ROA, ROE, and DER simultaneously have a significant effect on stock prices. Partially, ROA has no significant effect, ROE has a significant negative effect, while DER has a significant positive effect on stock prices. These findings suggest that the stock prices of IDX30 companies are determined not only by profitability but also by capital structure and broader market conditions that shape investors' expectations.